2019
DOI: 10.4038/cjs.v48i1.7587
|View full text |Cite
|
Sign up to set email alerts
|

Potentially zoonotic gastrointestinal parasites of dogs in Lunugala Tea estate community in Central Sri Lanka

Abstract: Coprological examination of gastrointestinal (GI) parasites and their life stages in humans and dogs and in soil was carried out in a low income tea estate community in the Central Province. This community has limited access to public health facilities and veterinary services and lives in close contact with free roaming dogs. Parasites in faeces were isolated and identified morphologically and morphometrically using microscopical methods, followed by molecular confirmation of selected protozoans. Soil samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
(29 reference statements)
2
3
0
1
Order By: Relevance
“…prevalence of nematode infections of the free-roaming dogs in Digana and Pussellawa (93.2%) was comparable to the prevalence (76-97%) recorded in previous studies (e.g., Hantana, Peradeniya and Talawakelle) in the country [15][16][17]24]. Sampled dogs were infected with both single (40.9%, n = 18 ) and mixed infections with two or more parasite species (52.3%, n = 23).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…prevalence of nematode infections of the free-roaming dogs in Digana and Pussellawa (93.2%) was comparable to the prevalence (76-97%) recorded in previous studies (e.g., Hantana, Peradeniya and Talawakelle) in the country [15][16][17]24]. Sampled dogs were infected with both single (40.9%, n = 18 ) and mixed infections with two or more parasite species (52.3%, n = 23).…”
Section: Discussionsupporting
confidence: 74%
“…In addition, the large number of free-roaming dogs in the neighbourhoods in Sri Lanka poses a serious public health risk to the communities. Although gastrointestinal parasites in both humans [13,14] and dogs [15][16][17] have been studied in different climatic areas of the country, the effect of soil temperature on the prevalence of different STNs has not been investigated comparatively.…”
Section: Introductionmentioning
confidence: 99%
“…Dogs are kept under homebased tethering (chaining or in a cage) and free roaming rearing methods ( 19 ). In this study, it was noted that there are specific dogs that do not belong to any of these two major systems and are referred to as “stray dogs.” Dogs that are not under anyone's management or ownership freely mingle with the community dogs, posing a risk to animal and public health ( 20 ). Indeed, all free roaming dogs pose a potential risk for disease transmission (in case of non-vaccination status) or other harm, even if they just roam during the night.…”
Section: Discussionmentioning
confidence: 99%
“…The eggs from these ascarids are common environmental contaminants of human habitation [10]. Higher rates of soil contamination (10-30%) with Toxocara eggs have been found globally in the vicinity where children commonly play, like backyards, playing grounds, and recreational parks, and viable eggs can survive for up to fifty-two weeks [11], [26] [45]. Mohammed [10] reported that out of 764 soil samples collected from relaxation parks in Abuja, Nigeria, helminth eggs were found in 68% of the samples studied.…”
Section: Prevalence Of Intestinal Helminth Infections Of Stray Dogs Omentioning
confidence: 99%